2015
DOI: 10.5498/wjp.v5.i1.56
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of psychological predictors of weight loss: How and what for?

Abstract: Obesity is a multifactorial disease and the prominent factors playing a role in its pathogenesis are biological, environmental and psychological. There is a growing interest in understanding psychological functioning of obese subjects and the influence of psychological factors on treatment outcome. The aim of the present narrative review is to critically analyze the current literature, in order to point out the most common psychological constructs studied in obesity and to give an overview of the main existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 114 publications
(142 reference statements)
0
41
0
4
Order By: Relevance
“…BSQ scores indicate how the individual views herself and incorporates a perceptual, attitudinal and behavioural component and thus may or may not be rooted in reality. It is a concept that is extremely relevant to research in obesity, as 74% of obese individuals have body image dissatisfaction and distortion (Lazzeretti et al., ). A study by Pona, Heinberg, Lavery, Ben‐Porath, and Rish () found that patients with pre‐existing mental health issues, such as depression or ideas of persecution were more likely to report body image concerns in the first 3 months after bariatric surgery, despite weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BSQ scores indicate how the individual views herself and incorporates a perceptual, attitudinal and behavioural component and thus may or may not be rooted in reality. It is a concept that is extremely relevant to research in obesity, as 74% of obese individuals have body image dissatisfaction and distortion (Lazzeretti et al., ). A study by Pona, Heinberg, Lavery, Ben‐Porath, and Rish () found that patients with pre‐existing mental health issues, such as depression or ideas of persecution were more likely to report body image concerns in the first 3 months after bariatric surgery, despite weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…The data show that slightly more than half of women who report a low concern about their body image also view themselves as "I-ex-obese" (n = 7, 58%). If we view as (Lazzeretti et al, 2015). A study by Pona, Heinberg, Lavery, Ben-Porath, and Rish (2016) found that patients with pre-existing mental health issues, such as depression or ideas of persecution were more likely to report body image concerns in the first 3 months after bariatric surgery, despite weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing understanding that this variability in response is rooted in the inherent variability of behavioral, biological, environmental, and psychosocial factors ; however, at present, we lack data sets that allow a comprehensive examination of how these multiple factors and their interactions influence treatment response. Some explanatory factors have emerged as potential predictors of treatment response and are summarized elsewhere , but few have been replicated across trials . Several reasons for this have been suggested, including heterogeneous study populations and treatments, imprecisely defined factors and the lack of common measures to assess them, insufficient frequency of longitudinal assessments, insufficient statistical power, and inadequate statistical modeling and analytic approaches .…”
Section: Introductionmentioning
confidence: 99%